2020
DOI: 10.33545/26174693.2020.v4.i1a.40
|View full text |Cite
|
Sign up to set email alerts
|

A possible correlation between low serum vitamin-D levels and type 2 diabetes mellitus

Abstract: Background: Diabetes Mellitus is a metabolic disease which continues to be a major public health concern. Vitamin D deficiency has been found to be associated with Diabetes Mellitus, decreased Insulin secretion and increased insulin resistance in animals and humans. Recent Research is now beginning to uncover the role of vitamin D in pancreatic beta cell function, Insulin action and inflammation. The beta cells of pancreas possess Vitamin D receptors and the enzyme 1 alpha Hydroxylase is expressed in pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
1
4
1
Order By: Relevance
“…After conducting this study, we detected that the level of vitamin D in the T2DM group, compared to the healthy group, was significantly lower. It can be concluded that there is a role for vitamin D in regulating blood sugar and improving insulin sensitivity by reducing insulin resistance [1]. This study correlates well with the study conducted by weeks, once a week, cheese with and without vitamin D were given to subjects that were randomly divided into two groups of 28,000 IU of vitamin D3 (VitD; n = 35) and placebo (n = 36).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…After conducting this study, we detected that the level of vitamin D in the T2DM group, compared to the healthy group, was significantly lower. It can be concluded that there is a role for vitamin D in regulating blood sugar and improving insulin sensitivity by reducing insulin resistance [1]. This study correlates well with the study conducted by weeks, once a week, cheese with and without vitamin D were given to subjects that were randomly divided into two groups of 28,000 IU of vitamin D3 (VitD; n = 35) and placebo (n = 36).…”
Section: Discussionsupporting
confidence: 74%
“…Vitamin D can play a role in keeping extracellular calcium levels normal, thereby controlling the flow of calcium through the cell membrane. Decreased serum vitamin D levels can affect and reduce the ability of calcium to secrete insulin [1]. In our study, serum calcium and phosphorus levels did not show a statistical significant difference with the control group.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Recent studies have investigated the possible involvement of vitamin D in the pathogenesis of diabetes and its related complication [7,8]. This fat-soluble vitamin's receptor has been discovered in pancreatic beta cells, implicating a possible function in insulin secretion [7,8]. Furthermore, insulin sensitivity and function have been linked to serum vitamin D levels [7].…”
Section: Introductionmentioning
confidence: 99%